International firms, national managers: the obstacles to migration of highly skilled labour in transnational corporations - Peixoto, João (1999)
Paper presented to ESRI Thematic Research Workshop on Economic Actors, National Systems and International Contexts, September 21-24, 1999, Copenhagen, Denmark (draft version)